Entrapment of metastable nanocrystals by polyoxometalates. Issue 29 (22nd March 2023) - Baranov, Mark; Duan, Yan; Leffler, Nitai; Avineri, Shani; Ezersky, Vladimir; Weinstock, Ira A.
Abstract : Entirely inorganic polyoxometalate ligands stabilize soluble macroanion-like complexes of metastable nanocrystalline cores. Abstract : Entirely inorganic polyoxometalate cluster-anion ligands are herein used to entrap and impart heat resistance to metastable metal-oxide based NCs. This is demonstrated by trapping 6-line ferrihydrite NCs that form as intermediates in the spontaneous conversion of β-FeOOH to hematite (α-Fe2 O3 ). The results suggest that polyoxometalate ligation may prove to be a general method for stabilizing metastable phases as the cores of entirely inorganic macro-anion like complexes.